BROAD-CHURCH HOMILETICS, KINGSLEY'S HYPATIA, AND THE CULTIVATED READER IN THE PEW. Issue 3 (30th August 2016) - Cook, Daniel
Abstract : The first issue and number of the Nineteenth Century, 1877, included a searching article by J. Baldwin Brown entitled "Is the Pulpit Losing Its Power?" Looking back over the decades, Brown marked a generational decline in England's preaching, which he argued had now been eclipsed by a print market distributing "freest discussion of the most sacred truths." Brown lamented that fewer talented men now joined the Anglican ministry, while the Church had increasingly withdrawn from the social mission which had animated mid-century preachers like Charles Kingsley (107–09). More troublingly, Brown speculated that modern Britons had become constitutionally averse to the homiletic situation. The preacher, he writes, often "seems as if he came down on the vast range of subjects which he is tempted to handle as from a superior height; and this is what the scientific mind can never endure. . . . [T]here has always been a sort of omniscient tone in the pulpit method of handling intellectual questions which stirs fierce rebellion in cultivated minds and hearts" (109–10). Brown pulls up short of blaming theology per se; for him its language of "above" and "beyond" has continuing relevance (110). Still, he broaches the possibility that by its very nature preaching risks antagonizing what current scholarship would term the "liberal subject": one which prizes freedom of conscience, empirical exploration, and debate.